If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-1+k4=-3
We move all terms to the left:
-1+k4-(-3)=0
We add all the numbers together, and all the variables
k^4+2=0
We do not support ekpression: k^4
| -2(x+4)=3(3x)-7 | | 27x+15-9x=3x-15 | | 2x(7+2x)=78 | | 7×x-15=69 | | (f-2)(3f-8)=0 | | 10=4(2x+3)+6 | | 3-4x=50-x | | 4x-10=3(x+6) | | 5a-19=1 | | 5x-5=3x+1x-1 | | 14x(-5)=90 | | 4(2x-7)=-8 | | 2x(5x-1)2-3x(5-1)=0 | | (8)/(10)=(x)/(9) | | 8.3-z=131.7 | | 4+3(2r+1)=19 | | -11a-6a=6+3+12a-9 | | 10j-8=-88 | | 6x+11=9+7x | | 10/2a=1 | | 1/2=3/4(2x-4/9) | | 9+4x−2=13x−11 | | 18+x+16=8x+20 | | 1=4-3y | | 49-2x=6x+52 | | 49-2x=-6x+52 | | 49-2x=-6+52 | | 6x+20x-16=18+16 | | 11x2-34x-21=0 | | 6x+20x-16=18x-16 | | 2l-6=3l-19 | | F=2(3n+4) |